Management Accounting Practices in the Era of Industry 4.0: Challenges and Opportunities for Business Innovation in Uzbekistan - Juraeva Mukhammadovna (Journal of Business Innovation and Accounting Research, 2025)
The advent of Industry 4.0 has fundamentally transformed management accounting practices globally, presenting both unprecedented challenges and opportunities for business innovation. This study examines the current state of management accounting practices in Uzbekistan within the context of digital transformation, analyzing the challenges faced by organizations and identifying opportunities for innovation. Utilizing a mixed-methods approach combining quantitative surveys and qualitative case studies, this research investigates how Uzbek enterprises are adapting their cost management systems, performance measurement frameworks, and decision-support mechanisms to align with Industry 4.0 requirements. The findings reveal that while Uzbekistan has made significant strides through initiatives such as the "Digital Uzbekistan 2030" strategy, substantial gaps remain between traditional accounting practices and the advanced methodologies required for competitive positioning in the global digital economy. The study identifies critical success factors including digital infrastructure development, human capital enhancement, and regulatory modernization. Furthermore, this research proposes an integrated framework for implementing innovative management accounting practices that leverage emerging technologies such as artificial intelligence, blockchain, big data analytics, and cloud computing. The results contribute to both theoretical understanding and practical guidance for organizations seeking to navigate the complexities of management accounting transformation in emerging economies.